The Education-Based Marketing Management in Drug Prevention Efforts in the Full Boarding Religious School Environment of Maahad Ahmadi Negeri Sembilan, Malaysia : Education-Based Marketing Management in Drug Prevention Efforts in the Full Boarding Religious School Environment of Maahad Ahmadi Negeri Sembilan, Malaysia - Lubis, Adelina; Effendi, Ihsan; Zulyadi, Rizkan; Arifin, Syasyain; Yudha Pratesta, Oxy (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Narcotics abuse is a serious problem that affects the younger generation, including students in boarding religious schools. This activity aims to develop and implement an educational program to prevent narcotics abuse in Maahad Ahmadi Negeri Sembilan, Malaysia. The methods used include seminars, workshops, and dissemination of information through social media and attractive posters. This program is designed to increase students' awareness and knowledge about the dangers of narcotics and provide strategies for refusing offers of abuse. The results of this activity show an increase in students' understanding of narcotics issues and their ability to make better decisions. By involving all parties, including teachers, parents and the community, it is hoped that this activity can create a safer and more positive environment for students at Maahad Ahmadi